2017
DOI: 10.1038/s41598-017-11954-y
|View full text |Cite
|
Sign up to set email alerts
|

End-Cretaceous akaganéite as a mineral marker of Deccan volcanism in the sedimentary record

Abstract: An enigmatic chloride-rich iron (oxyhydr)oxide has been recently identified together with mercury anomalies in End-Cretaceous marine sediments coeval with the Deccan Traps eruptions. The mineral was observed in Bidart (France) and Gubbio (Italy), suggesting a widespread phenomenon. However, the exact nature and origin of this Cl-bearing mineral remained speculative. Here, we characterized the accurate composition and nanostructure of this chloride-rich phase by using micro-Raman spectroscopy, Transmission (TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
(50 reference statements)
2
12
0
Order By: Relevance
“…On Earth, akaganeite often appears as the corrosion product of metallic Fe or Fe(II) in acidic Cl‐rich oxidation conditions (Bibi et al., 2011) and has been found in Cl‐rich environments including soils drained of acidic water, hot brines, marine environments, sediment of sulfur‐rich oxides, carbonate concretion, Fe‐Ni meteorites and even Fe‐rich archeological sites (Buchwald & Clarke, 1989; Font et al., 2017; Réguer et al., 2007). These conditions are distinctly different from the conditions under which allophane typically occurs.…”
Section: Discussionmentioning
confidence: 99%
“…On Earth, akaganeite often appears as the corrosion product of metallic Fe or Fe(II) in acidic Cl‐rich oxidation conditions (Bibi et al., 2011) and has been found in Cl‐rich environments including soils drained of acidic water, hot brines, marine environments, sediment of sulfur‐rich oxides, carbonate concretion, Fe‐Ni meteorites and even Fe‐rich archeological sites (Buchwald & Clarke, 1989; Font et al., 2017; Réguer et al., 2007). These conditions are distinctly different from the conditions under which allophane typically occurs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] The formation of akaganeite occurs in environments under acidic oxidizing conditions (pH 1–3) as precipitate in chloride rich and acid environments. [ 10 ] Instead, in alkaline media, akageneite can be transformed to goethite and hematite. [ 11 ] Some studies [ 12,13 ] indicated that chlorine does not participate directly in the mechanism of electrochemical reactions, but it plays an indirect role in the corrosion process due to its high hygroscopicity that increases the conductivity of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Solution pH and Cl − concentration are the dominant factors controlling akaganeite formation in terrestrial environments (Cornell & Schwertmann, ). Natural akaganeite usually forms through oxidation of Fe(II) and metallic Fe to Fe(III) followed by Fe(III) hydrolysis to akaganeite under chloride‐rich acidic conditions in hot brines, marine environments, oxidized sulfide‐rich sediments, carbonate concretions, meteorites, volcanic rocks, and plumes (Bibi et al, ; Buchwald & Clarke, ; Font et al, ; Johnston, ; Mackay, ; Morris et al, ; Pye, ). Synthetic akaganeite forms through forced hydrolysis of 0.1–2 M Fe(III) chloride solutions at room temperature (RT) or at elevated temperatures (40–120 °C) under acidic (initial pH < 2) conditions (Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%